2013
DOI: 10.1002/admi.201300026
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic Coatings on Cellulose‐Based Materials: Fabrication, Properties, and Applications

Abstract: Wettability of a solid surface by a liquid plays an important role in several phenomena and applications, for example in adhesion, printing, and self‐cleaning. In particular, wetting of rough surfaces has attracted great scientific interest in recent decades. Superhydrophobic surfaces, which possess extraordinary water repelling properties due to their low surface energy and specific nanometer‐ and micrometer‐scale roughness, are of particular interest due to the great variety of potential applications ranging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
165
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(166 citation statements)
references
References 128 publications
(215 reference statements)
1
165
0
Order By: Relevance
“…20,21 Homogeneous liquid-repellent coatings on cellulose-based materials were extensively reported on superhydrophobicity and/or oleophobicity recently. 22,23 Only a few studies 13,14,18,24 have reported surfaces performing higher oil contact angles than that of water, most all of which, however, are oleophilic thus displaying limited oil repellency. To obtain counterintuitive superhydrophilicity on an oil-repellent surface, the introduction and regulation of heterogeneity in surface chemistry plays a vitally important role.…”
Section: 19mentioning
confidence: 97%
“…20,21 Homogeneous liquid-repellent coatings on cellulose-based materials were extensively reported on superhydrophobicity and/or oleophobicity recently. 22,23 Only a few studies 13,14,18,24 have reported surfaces performing higher oil contact angles than that of water, most all of which, however, are oleophilic thus displaying limited oil repellency. To obtain counterintuitive superhydrophilicity on an oil-repellent surface, the introduction and regulation of heterogeneity in surface chemistry plays a vitally important role.…”
Section: 19mentioning
confidence: 97%
“…Plasma is the fourth state of matter in the universe, ionised gas or free electrons, bombarded on the surface with high energy under the electric field/super magnetic field so that it cuts the link between carbon, hydrogen and oxygen and making the surface into nanoroughed surface [45,74]. This method is highly targetive, selective and a controlled process and further selective deposition can be achieved through chemical vapour deposition method.…”
Section: Plasma Etchingmentioning
confidence: 98%
“…However, it is hydrophilic and hygroscopic, which makes it difficult to beat the success of synthetic plastic materials without further modification. A wide range of studies have examined surface alteration approaches to modify and tune barrier properties of cellulosic surfaces [1][2][3][4][5][6][7][8][9][10][11] . These methods involve morphological and chemical modifications by plasma processing [1][2][3] , deposition of organic and inorganic coatings 4,8 , chemical vapor deposition 9 , and polymerization techniques 10 .…”
Section:  Introductionmentioning
confidence: 99%